Robust nonfullerene solar cells approaching unity external quantum efficiency enabled by suppression of geminate recombination - Derya Baran (Nature Portfolio, 2018)
The nonfullerene-based small molecules start to attract more attention for solar cell research than the fullerene acceptors due to their wider tunability. Here Baran et al. demonstrate nonfullerene-based solar cells with high power conversion efficiency of 12% and quantum efficiencies approaching 100%.